First on-sky demonstration of an integrated-photonic nulling interferometer: the GLINT instrument. Issue 3 (23rd November 2019) - Norris, Barnaby R M; Cvetojevic, Nick; Lagadec, Tiphaine; Jovanovic, Nemanja; Gross, Simon; Arriola, Alexander; Gretzinger, Thomas; Martinod, Marc-Antoine; Guyon, Olivier; Lozi, Julien; Withford, Michael J; Lawrence, Jon S; et al.
ABSTRACT: The characterization of exoplanets is critical to understanding planet diversity and formation, their atmospheric composition, and the potential for life. This endeavour is greatly enhanced when light from the planet can be spatially separated from that of the host star. One potential method is nulling interferometry, where the contaminating starlight is removed via destructive interference. The GLINT instrument is a photonic nulling interferometer with novel capabilities that has now been demonstrated in on-sky testing. The instrument fragments the telescope pupil into sub-apertures that are injected into waveguides within a single-mode photonic chip. Here, all requisite beam splitting, routing, and recombination are performed using integrated photonic components. We describe the design, construction, and laboratory testing of our GLINT pathfinder instrument. We then demonstrate the efficacy of this method on sky at the Subaru Telescope, achieving a null-depth precision on sky of ∼10 −4 and successfully determining the angular diameter of stars (via their null-depth measurements) to milliarcsecond accuracy. A statistical method for analysing such data is described, along with an outline of the next steps required to deploy this technique for cutting-edge science.